ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI RISK MANAGEMENT DISCLOSURE (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2014) - Sulistyaningsih Sulistyaningsih; Barbara Gunawan (Riset Akuntansi dan Keuangan Indonesia, 2016)
This  study  was  to  analyze  the  effect  of  management  ownership,  public ownership, commissioner size, auditor reputation, leverage and firm size to the risk management dislosure in the annual report. The population in this study is a manufacturing company that listed on indonesia stock exchange in 2012 to 2014. Sampling technique was done by purposive sampling. The number of manufacturing companies that used sampel of 34 companies for a total study sample was 102 annual report. The analytical method used was multiple regression analysis using SPSS 15.0The results of this study indicate that public ownership has significant effect positively and significant degree is 0,041. Commissioner size has significant effect positively and significant  degree  0,001.  While  the  management  ownership,  auditor  reputation, leverage, and firm size didn’t have significant effect on risk management disclosure in the annual report..